1997
DOI: 10.1056/nejm199703133361101
|View full text |Cite
|
Sign up to set email alerts
|

Acute Non-A–E Hepatitis in the United States and the Role of Hepatitis G Virus Infection

Abstract: The evidence from this surveillance study does not implicate HGV as an etiologic agent of non-A-E hepatitis. Persistent infection with HGV was common, but it did not lead to chronic disease and did not affect the clinical course in patients with hepatitis A, B, or C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
252
4
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(282 citation statements)
references
References 23 publications
21
252
4
3
Order By: Relevance
“…They did not appear to be related to HGV infection because the frequency of HGV-RNA detection was similar among the non-ABC hepatitis cases, the hepatitis C cases, and the non-hepatitis controls, as has been previously reported. 25,26 This suggests that these non-ABC cases were either misdiagnosed as viral hepatitis, that the levels of anti-HCV were too low to detect during the initial illness, or that yet another transfusion-transmitted virus exists, a prospect clearly warranting further study. It is noteworthy that 10% of the non-ABC cases progressed to chronic hepatitis, with cirrhosis shown in 1 of the 4 that were biopsied.…”
Section: Discussionmentioning
confidence: 99%
“…They did not appear to be related to HGV infection because the frequency of HGV-RNA detection was similar among the non-ABC hepatitis cases, the hepatitis C cases, and the non-hepatitis controls, as has been previously reported. 25,26 This suggests that these non-ABC cases were either misdiagnosed as viral hepatitis, that the levels of anti-HCV were too low to detect during the initial illness, or that yet another transfusion-transmitted virus exists, a prospect clearly warranting further study. It is noteworthy that 10% of the non-ABC cases progressed to chronic hepatitis, with cirrhosis shown in 1 of the 4 that were biopsied.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery in 1998 of the possible benefit to survival and slowing of progression to AIDS among HIV infected patients who are co-infected with GBV-C [Heringlake et al, 1998] provided renewed interest in the seemingly harmless GB virus C [Alter et al, 1997;Alter, 2004]. Numerous studies reported a protective effect of GBV-C and HIV co-infection, though a few studies have observed no effect [Tillmann and Manns, 2001;Stapleton et al, 2004].…”
Section: Biological Relevance Of Gbv-c Genotypesmentioning
confidence: 99%
“…Among subjects with HGV exposure (HGV RNA plus anti-E2 positive), a whether HGV is associated with liver disease. 5 To assess the association of hepatocellular carcinoma (HCC) with HGV greater proportion of cases (40%) than controls (14%) had transfusion history. The possible role of HGV in HCC etiology infection, we carried out a hospital-based case-control study in the province of Brescia, an area in northern Italy with one seems modest because the population-attributable risk is lower (4%) than those for HBsAg (22%), HCV RNA (36%), of the highest incidence rates of HCC in Europe.…”
mentioning
confidence: 99%